Thermal decomposition of mixed calcium oxalate hydrates – kinetic deconvolution of complex heterogeneous processes. Issue 16 (14th April 2020) - Svoboda, Roman; Olmrová Zmrhalová, Zuzana; Galusek, Dušan; Brandová, Daniela; Chovanec, Jozef
Abstract : Whereas thermogravimetry monitors only a single-step CaOx decomposition reaction, DSC in addition reveals the complex competing CO oxidation kinetics. Abstract : Differential scanning calorimetry (DSC), thermogravimetry (TG) and in situ XRD were used to study dehydration and consequent decomposition reactions of mixed calcium oxalate hydrates. As the complex dehydration kinetics exhibited certain trends with respect to the applied heating rate, the modified multivariate kinetic analysis approach (based on averaged curve-by-curve optimizations) was employed to obtain a full kinetic description of the data. The Šesták–Berggren equation was used to model the two consequent dehydration reactions. Good agreement was found between the kinetic parameters calculated from the DSC and TG data – approximate values of activation energies were 68 and 81 kJ mol −1 for the trihydrate → monohydrate and monohydrate → anhydride transformations, respectively. A procedural methodology was developed to predict both dehydration kinetics and hydrate content ratios. For the calcium oxalate decomposition the TG technique provided very precise single-step prediction with an activation energy of 180 kJ mol −1 . DSC on the other hand provided complex information on joint decomposition and carbon monoxide oxidation reactions – the proposed reaction mechanism includes completion of two reaction paths composed of consequent chemical reactions. A mechanistic view of the complex reaction path is discussed in terms of the diffusion barrier limiting the oxidation step.